Intra-operative reliability of ShapeMatch cutting guide placement in total knee arthroplasty*. (5th March 2013) - Clark, Gavin; Leong, Anthony; McEwen, Peter; Steele, Robert; Tran, Ton; Trivett, Adrian
Abstract : Custom cutting guides based on pre-operative imaging have been introduced for total knee arthroplasty (TKA). The aim of this prospective cohort study was to assess the reliability of repeated placement of custom cutting guides by multiple surgeons in a group of patients undergoing TKA. Custom cutting guides (ShapeMatch®, Stryker Orthopaedics) were designed from pre-operative MRI scans. The treating surgeon placed each guide on the femur and tibia of each patient three times without pinning the block. The three-dimensional position and orientation of the guide was measured for each repetition using a computer navigation system. The surgeon was blinded to the navigation system display. Data from 24 patients and 6 surgeons were analyzed. Intraclass correlation coefficients for all measurement parameters were in the range 0.889–0.997 (excellent), and all comparisons were statistically significant ( p  < 0.001). The range for femoral varus/valgus was 0.0–1.5°, with 96% of patients being within 0.5°. For femoral flexion/extension the range was 0.0–3.5° (92% within 2.5°). On the tibia, varus/valgus had a range of 0.0–1.0° (92% within 0.5°), and for slope the range was 0.0–3.5° (92% within 2.5°). The high degree of agreement indicated that intra-surgeon variation was minimal and that the technique is reliable.